2013
DOI: 10.15517/rbt.v57i1-2.11323
|View full text |Cite
|
Sign up to set email alerts
|

Wood anatomy of tribe Detarieae and comparison with tribe Caesalpinieae (Leguminosae, Caesalpinioideae) in Venezuela

Abstract: We studied the wood anatomy of 29 species belonging to 10 genera of the tribe Detarieae, subfamily Caesalpinioideae and compare them with tribe Caesalpinieae. Detarieae is the largest of four tribes of Caesalpinioideae, with 84 genera, only eleven occur in Venezuela with species of timber importance. The specimens were collected in Venezuela and include wood samples from the collection of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 12 publications
2
14
0
9
Order By: Relevance
“…Canessa (1989) agreed with our results in Copaifera species; he found that the axial parenchyma in C. camibar was different than that of C. officinalis and C. pubiflora. Parenchyma is reported to be vasicentric, aliform to confluent, and aliform of the lozenge type in these species (Melandri & Espinoza de Pernía 2009). The ray dimensions and axial parenchyma of some Copaifera species are characterized by high anatomy variation (Regina et al 2002), and our results confirm that.…”
Section: Discussionsupporting
confidence: 84%
“…Canessa (1989) agreed with our results in Copaifera species; he found that the axial parenchyma in C. camibar was different than that of C. officinalis and C. pubiflora. Parenchyma is reported to be vasicentric, aliform to confluent, and aliform of the lozenge type in these species (Melandri & Espinoza de Pernía 2009). The ray dimensions and axial parenchyma of some Copaifera species are characterized by high anatomy variation (Regina et al 2002), and our results confirm that.…”
Section: Discussionsupporting
confidence: 84%
“…vageleri, H. courbaril e H. oblongifolia. La especie C. martiana presenta anillos de crecimiento defi nidos por bandas de parénquima asociadas a banda de madera tardía, confi rmando parte de la información reportada por Melandri & Espinoza (2009); sin embargo, estos anillos presentan difi cultad para la diferenciación. Igualmente, se observan anillos de crecimiento defi nidos por la ausencia de poros en una zona angosta de la madera tardía en C. glaberrima, K. malaccensis y P. pubescens, por disposición más compacta de las bandas de parénquima en la madera tardía en D. guianense y por banda de madera tardía de coloración más oscura en T. polyphylla confi rmando la información registrada por Espinoza Melandri (2006).…”
Section: Descripción Anatómicaunclassified
“…Únicamente D. guianense registró parénquima reticulado en bandas confi rmando lo descrito por Detienne & Jacquet (1983) y Höhn (1999). La especie C. martiana, presentó parénquima apotraqueal difuso y en bandas, característica que es común a otras especies de este género confi rmando lo descrito por Melandri & Espinoza (2009).…”
Section: Descripción Anatómicaunclassified
See 2 more Smart Citations